2001
DOI: 10.1051/0004-6361:20000340
|View full text |Cite
|
Sign up to set email alerts
|

UV photodestruction of CH bonds and the evolution of the 3.4 $\mathsf{\mu}$m feature carrier

Abstract: Abstract. We present the results of a laboratory program aimed at studying the effects induced by energetic UV photons on hydrogenated carbon particles. Experiments have been performed under simulated diffuse and dense interstellar medium conditions. To monitor the effects of UV irradiation on grains IR spectroscopy has been used. In both circumstances UV photons lead to a reduction of the aliphatic 3.4 µm band. An estimation of the destruction cross section by UV photons for the hydrogenated carbon particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 31 publications
3
84
0
Order By: Relevance
“…Muñoz-Caro and collaborators have simulated analogs of carbonaceous dust grains in dense and diffuse interstellar medium. Mennella et al (2001) have found that the irradiated hydrogenated carbon grains coated with H 2 O or H 2 O+CO+NH 3 ice layer (as an analog of dust in the dense interstellar medium) have higher reduction than those coated with the Ar ice layer (as an analog of dust in the diffuse interstellar medium). On the other hand, for a similar analog for dust in the dense and diffuse interstellar medium, Muñoz-Caro et al (2001) have found that hexane samples covered with H 2 O ice layer have lower reduction than those covered with the Ar ice layer.…”
Section: The 3-8 μM Spectral Rangementioning
confidence: 99%
“…Muñoz-Caro and collaborators have simulated analogs of carbonaceous dust grains in dense and diffuse interstellar medium. Mennella et al (2001) have found that the irradiated hydrogenated carbon grains coated with H 2 O or H 2 O+CO+NH 3 ice layer (as an analog of dust in the dense interstellar medium) have higher reduction than those coated with the Ar ice layer (as an analog of dust in the diffuse interstellar medium). On the other hand, for a similar analog for dust in the dense and diffuse interstellar medium, Muñoz-Caro et al (2001) have found that hexane samples covered with H 2 O ice layer have lower reduction than those covered with the Ar ice layer.…”
Section: The 3-8 μM Spectral Rangementioning
confidence: 99%
“…The C 2 H 2 and HCN spectra are also calculated using the HITRAN database (Rothman et al 1998) and shown in the bottom of the panel. et al (1995) but in the diffuse ISM where the destruction of C-H bonds by UV photolysis is equilibrated by rehydrogenation with ample atomic hydrogen (Mennella et al 2001(Mennella et al , 2002. Tielens et al (1994) proposed a similar mechanism for the formation of aliphatic C-H bonds by hydrogenation of a graphite surface amorphized by the ion bombardment in the interstellar shocks.…”
Section: Variations Of Aliphatic and Aromatic Abundancementioning
confidence: 99%
“…In diffuse clouds, an interstellar radiation flux of about 8 × 10 7 photons cm −2 s −1 (Mathis et al 1983), combined with σ d,UV found by Mennella et al (2001), gives a characteristic destruction time by exposure to UV radiation t diffuse d,UV = 4 × 10 3 years, a time much shorter than for the destruction by cosmic rays. The destruction of the interstellar 3.4 μm feature in diffuse medium is thus most probably caused by the UV field in these regions rather than by CR interactions.…”
Section: Diffuse Interstellar Mediummentioning
confidence: 99%
“…The destruction of C-H bonds by UV irradiation has been studied by Muñoz Caro et al (2001) in hydrocarbon molecules and by Mennella et al (2001) in hydrocarbon grains. They found a destruction cross section σ d,UV = 1.0 × 10 −19 cm 2 /photon.…”
Section: Evolution Of the 34 μM Feature Between Diffuse And Dense Phmentioning
confidence: 99%